2007
DOI: 10.1186/1472-6831-7-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Persian version of the OIDP index

Abstract: BackgroundMeasuring the impacts of oral conditions on quality of life is an important part of oral health needs assessment. For this purpose a variety of oral health-related quality of life instruments have been developed. To use a scale in a new context or with a different groups of people, it is necessary to re-establish its psychometric properties. The objectives of this study are to develop and test the reliability and validity of the Persian version of Oral Impacts on Daily Performances (OIDP) index.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
47
3
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 21 publications
12
47
3
6
Order By: Relevance
“…Consequently, locality of residence might have affected the response patterns, although the sample size was not enough for confirmation Table 1 Prevalence of oral health problems and oral impacts on daily performances Table 2 Item-scale correlations for the OIDP items of the findings. A previous study using another language version of the OIDP has also reported skewed responses to some items (14). Analysis of the relationship between response patterns and subjects' characteristics could be important under various settings.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Consequently, locality of residence might have affected the response patterns, although the sample size was not enough for confirmation Table 1 Prevalence of oral health problems and oral impacts on daily performances Table 2 Item-scale correlations for the OIDP items of the findings. A previous study using another language version of the OIDP has also reported skewed responses to some items (14). Analysis of the relationship between response patterns and subjects' characteristics could be important under various settings.…”
Section: Discussionmentioning
confidence: 92%
“…Three versions of the OIDP have been developed and translated into several languages, including an interview and self-administered questionnaire for adults, and a separate one for children (14)(15)(16)(17)(18)(19). The interview and self-administered questionnaire both assess the degree to which oral health problems have affected the life of the participant over the previous 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 250 white-collar workers in the port with mean age of 34.67 ± 6.36 participated in the study. Dorri et al [12] examined the validity and reliability of the OIDP inventory among Iranian 20-50-yearold employees in Mashhad [12]. In the present study, all participants explained that oral and dental problems had affected at least one of their daily activities.…”
Section: Discussionmentioning
confidence: 72%
“…It was also below 70% observed in Western population with high dental disease levels and in a low oral disease Thai population [10]. Different values have been reported for the prevalence of OIDP by Kida et al [13] (51.2% in urban and 61.2% in rural areas), Dorri et al [12] (64.9%), Srisilapanan and Sheiham [14] (52.8%), Jung et al [15] (62.9%). The 8 impact prevalence rates ranged from 4.4% to 48.4%.…”
Section: Discussionmentioning
confidence: 80%
“…Od pojave originalne verzije, OIDP je korišćen u različitim studijama kod adultne populacije u Velikoj Britaniji i Grčkoj 12, 14 , Tajlandu 15 , Tanzaniji 16 , Ugandi 17 , Norveškoj 18 i Iranu 19 . Ovaj upitnik je usvojen za epidemiološka istraži-vanja populacija različitog doba i pokazalo se da je pouzdan i valjan.…”
Section: Uvodunclassified